How the green and digital transitions are reshaping the automotive ecosystem - Dechezleprêtre, Antoine (OECD Publishing, 2023)
The automotive sector is important across OECD countries in terms of value-added and R&D, but is also heavily affected by the green and the digital transformations. This paper offers a novel and holistic view of the automotive sector and its surrounding ecosystem based on a combination of Inter-Country Input-Output (ICIO) tables, patent data, mergers and acquisitions (M&A) transactions, cross-country micro-distributed data and firm-level balance sheet data. It identifies the boundaries of this industrial ecosystem including connected sectors (e.g. upstream and downstream) as well as knowledge and technology providers (e.g. universities or the digital industry). The paper documents emerging trends at the geographical and technological levels and provides a comprehensive assessment of the ecosystem's changing microstructure, with a growing role of young and digital-intensive companies. Finally, it provides recommendations for effective public policies to support the automotive ecosystem, with a focus on innovation, competition and the growth of young firms
Keywords: Environment; Science and Technology; Industry and Services